Proteksionisme Nikel Indonesia dalam Perdagangan Dunia - Radhica, Dicky Dwi (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2023)
Indonesia plays a vital role in the global nickel industry, with the world's largest nickel reserves of 52%. Indonesia's nickel production has increased every year. Indonesia issued a policy of Minister of Energy and Mineral Resources Number 11 of 2019 concerning downstream nickel. Nickel downstream is an act of protectionism or limiting nickel exports in world trade. The purpose of this study is to analyze the reasons why Indonesia has taken protectionist measures against its nickel. To answer the objectives of this study, the method used by researchers is a descriptive analysis method with a qualitative approach and protectionism theory through national policy variables and national interests, as well as by comparing world nickel demand and potential and identifying changes in national policies in supporting nickel added value. The research results show that Indonesia carries out downstream as a form of protectionism in maximizing the country's potential to boost economic growth. The efforts made by the Indonesian government are to increase the production of electric batteries in the country rather than exporting raw nickel. However, the implementation of downstream in Indonesia is still facing challenges such as uneven construction of smelters and inadequate quality of human resources. Therefore, policy recommendations are focused on increasing smelter development in Indonesia. Therefore, the Government of Indonesia must develop human resource skills.